Systematic Literature Review: Governance Performance of Amil Zakat Institutions by Measuring the Indonesian Magnificence of Zakat (IMZ) - Nurwahyuni, Hanifah; Fatikah, Nurul Izza; Simorangkir, Melisa Ratu Annastasya; Syahida, Syarifah; Febriani, Dewi; Sulhani (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
Zakat is a manifestation of faith in Allah and a form of concern for others. Zakat can be a solution in solving social and economic problems. Indonesia is the largest Muslim country in the world with 236 million Muslims or 84.35 percent of Indonesia's total population. Thus, the potential for zakat in Indonesia is very large. Fadillah (2011) stated that the large potential for zakat in Indonesia cannot yet be managed well. This research was conducted to examine and identify factors and forms of good governance of zakat amil institutions in Indonesia, using special measurements. Indonesia Magnificence of Zakat (IMZ). This research uses the Systematic Literature Review (SLR) research method. This research emphasizes how important it is to foster public trust through transparency and accountability, as well as how important it is to apply a creative approach to zakat collection and distribution so that the impact of zakat is optimal for society.